Effects of cGMP/Akt/GSK-3β signaling pathway on atrial natriuretic peptide secretion in rabbits with rapid atrial pacing - Cao, Shuxia; Han, Chengyong; Xuan, Chunhua; Li, Xiangdan; Wen, Jing; Xu, Dongyuan (Frontiers in Physiology, 2022)
Atrial natriuretic peptide (ANP) plays a pivotal role in the regulation of cardiovascular system. ANP level increases during atrial fibrillation (AF), suggesting that AF may provoke ANP secretion, but its potential mechanism is still unclear. In the present study, the potential mechanisms of rapid atrial pacing (RAP) regulating ANP secretion was explored. Rabbits were subjected to burst RAP, ANP secretion increased whereas cyclic guanosine monophosphate (cGMP) concentrations decreased during RAP. p-Akt and p-GSK-3β levels decreased in atrial tissues. Natriuretic peptide receptor A (NPR-A) protein and particulate guanylate cyclase (PGC) activity were detected. The sensitivity of NPR-A to ANP decreased, leading to the PGC activity decreased. Also, isolated atrial perfusion system were made in the rabbit model, cGMP was shown to inhibit ANP secretion, and the Akt inhibitor LY294002 (LY) and GSK-3β inhibitor SB216763 (SB) attenuated the inhibitory effects of cGMP on ANP secretion and enhanced the inhibitory effects of cGMP on atrial dynamics. In conclusion, NPR-A interacts with ANP to regulate PGC expression, and influence the expression of cGMP during RAP, which involves in Akt/GSK-3β signaling pathway.